Antiadhesive Property of Photoreactive Azidophenyl Low-Molecular-Weight Chitosan in Rabbit Laminotomy Model. (24th March 2013) - Kim, Jong Won; Song, Kwang-Sup; Kang, Hyun; Jang, Eui-Chan; Kim, Mi Kyung; Son, Tae Il
Abstract : Newly developed photoreactive azidophenyl chitosan (P-ALMC) has characteristics of a transformable gel type and its outer layer could be sealed up like a film after UV radiation. We aim to evaluate the antiadhesive properties of P-ALMC through comparing it with hyaluronic acid-carboxymethylcellulose membrane (HA-CMC) in a rabbit laminotomy model. Laminotomies were performed at the L3-4, L4-5, and L5-6 levels in 41 rabbits and each level was randomly assigned to either receive saline (group I), HA-CMC (group II), or P-ALMC (group III). The extent of peridural fibrosis, density of fibroblasts and inflammatory cells, and dural thickness were evaluated at 6 and 12 weeks postoperatively. In the groups II and III, the extents of peridural fibrosis and dural thickness were significantly smaller than those in group I (P < 0.001 ) and no differences between groups II and III were found at the postoperative 6 and 12 weeks. There were no differences of cell density among groups. P-ALMC showed effective antiadhesive properties comparable to HA-CMC and could be one of the candidates as an anti-adhesive agent for spine surgery even further study is required to identify the effectiveness of its unique characteristics as mechanical barrier.